Study on weak link of energy utilization in oil transfer station system: Insights from energy level analysis method - Qinglin Cheng; Zhidong Li; Daming Song; Wei Gao; Hao Wu; Hongjun Xie; Youwang Chen; Limin Gu; Yang Liu (Energy Reports, 2020)
In this paper, an energy level analysis model of oil transfer station system is established, which is divided into oil transfer station subsystem and pipeline network subsystem. From the perspective of the level of energy, the system is evaluated and optimized by virtue of using energy level analysis method and combining with the "three box" analysis model. Moreover, the energy level evaluation indexes of import and export, energy level difference and energy level balance coefficient, are calculated in terms of the calculation results. Then the energy utilization diagrams (EUD) are drawn, it can be seen that more than 95% of the supply energy in the oil transfer station subsystem is provided by gas. The energy level difference of the heating furnace is the largest, which can be seen intuitively that the heating furnace is the weak link of energy utilization in the whole system. Based on the influencing factors, the corresponding energy saving and consumption reduction measures are preliminarily proposed.
Keywords: 330; "Three box" analysis; Energy level analysis; EUD; Oil and gas gathering and transportation system